GAGASAN PENGEMBANGAN DESA WISATA BERBASIS BUDAYA LOKAL DAERAH UNTUK MENGEMBANGKAN KEARIFAN LOKAL DAERAH - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This study aims: 1) to socialize the development of local culture-based tourist villageas a solution to develop local wisdom of Bali area, and 2) to socialize the development of localculture-based tourist village by highlighting the local area that can provide convenience for therelated areas and directly impact the development and preservation of Balinese culture. Themethod used in the writing of this idea is the method of literature review with descriptive analysis.This is done by examining the various literature (sources of libraries and internet) associatedwith the proposed idea. Opportunities for implementation of this idea is the existence of thegovernment’s support capacity to socialize it to the community and provide assistance facilitiesand infrastructure and the active role of the community who independently manage the regionbased on local wisdom of their respective regions. Currently the tourism sector provides asubstantial income for development in Indonesia. The contribution of tourism from year to yearis increasing. Bali is one of the areas in Indonesia that has such potential. Physically Bali isfamous for the beauty of the dominant region is still beautiful and still thick wrapped by a veryunique culture. Bali is famous for its cultural beauty. Balinese culture is not only limited tocertain aspects but rather complex and includes various human activities. The result of researchthat is 1) the existence of tourist villages in Bali will bring back the values of local wisdom inone area that may have previously been ignored and 2) people can recognize the local culturethey have and have the ability to develop local village wisdom based on the potential that existsin their respective regions - each.